Schizophrenia-like behavior is not altered by melatonin supplementation in rodents - ARLINDO C. AFONSO; FELIPE D. PACHECO; LARA CANEVER; PATRICIA G. WESSLER; GUSTAVO A. MASTELLA; AMANDA K. GODOI; ISABELA HUBBE; LAURA M. BISCHOFF; ALEX VICTOR S. BIALECKI; ALEXANDRA I. ZUGNO (Anais da Academia Brasileira de Ciências, 2020)
Abstract An emerging area in schizophrenia research focuses on the impact of immunomodulatory drugs such as melatonin, which have played important roles in many biological systems and functions, and appears to be promising. The objective was to evaluate the effect of melatonin on behavioral parameters in an animal model of schizophrenia. For this, Wistar rats were divided and used in two different protocols. In the prevention protocol, the animals received 1 or 10mg/kg of melatonin or water for 14 days, and between the 8th and 14th day they received ketamine or saline. In the reversal protocol, the opposite occurred. On the 14th day, the animals underwent behavioral tests: locomotor activity and prepulse inhibition task. In both protocols, the results revealed that ketamine had effects on locomotor activity and prepulse inhibition, confirming the validity of ketamine construction as a good animal model of schizophrenia. However, at least at the doses used, melatonin was not able to reverse/prevent ketamine damage. More studies are necessary to evaluate the role of melatonin as an adjuvant treatment in psychiatric disorders.